Characters Association and Path Coefficient Analysis among Quantitative Traits of Chrysanthemum (Dendranthema×Grandiflora Tzvelev) - Gurung, Anamika; Kumar, Rajiv; Aswath, C.; Prakash, Tejaswini; Bennurmath, Parvathi; Manamohan, M.; Reddy, D. C. Lakshmana (International Journal of Bio-resource and Stress Management, 2022)
The present experiment was carried out under naturally ventilated polyhouse at the experimental farm of Division of Flower and Medicinal Crops, ICAR-Indian Institute of Horticultural Research, Bengaluru, Karnataka, India for two years during 2019 (August-November) and 2020 (August-December) The experiment was laid out in completely randomized design (CRD) with three replications under naturally ventilated polyhouse. Analysis of variance showed significant differences among genotypes for all the traits. Results revealed that the days to optimum flowering exhibited positive and significant correlation with plant height (0.599), days to bud initiation (0.628), days to first flower opening (0.985) and flowering duration (0.571), whereas, positive significant correlation with flower diameter (0.324). The results of path coefficient analysis using correlation coefficients revealed that days to first flower opening (1.033) exhibited positive and very high direct effect on days to optimum flowering while, number of leavesplant-1 (0.040), days to bud initiation (0.056), flower diameter (0.025) and flower duration (0.022) showed positive and negligible direct effect. Therefore, the selection on the basis of traits viz., plant height, days to bud initiation, days to first flower opening, flower duration and flower diameter will be more effective for improvement of the flowering traits in chrysanthemum breeding.